HIDUP DIPIMPIN OLEH ROH KUDUS MENURUT SURAT GALATIA 5:16-18 - Waruwu , Yasni (GENEVA: JURNAL TEOLOGI DAN MISI, 2024)
A life led by the Holy Spirit is a life filled with the Holy Spirit in the sense that believers continue to walk in the Spirit. Paul commands us through Galatians 5:16-18 that we must give ourselves to be led by the Holy Spirit. Because for Paul to live being led by the Holy Spirit means living in accordance with God's will and being able to do the truth that has been revealed through his only begotten son, Christ. Life led by the Holy Spirit is defined by three theories. First, according to John Bevere and Addison Bevere who say that a life led by the Holy Spirit means that the Holy Spirit will reveal all the truth of God to us. That is why it is important for us to invite the Holy Spirit to be present within us. Second, according to Elmer L. Towns, who said that a life led by the Holy Spirit means that the Holy Spirit will make us holy before God and in perfect condition before God. Third, according to J. Wesley Brill who said that a life led by the Holy Spirit means that the Holy Spirit invites and leads us in holiness.